Italian association for the study of the liver position statement on SARS-CoV2 vaccination. Issue 6 (June 2021) - Russo, Francesco Paolo; Piano, Salvatore; Bruno, Raffaele; Burra, Patrizia; Puoti, Massimo; Masarone, Mario; Montagnese, Sara; Ponziani, Francesca Romana; Petta, Salvatore; Aghemo, Alessio; ,
Abstract: The vaccination campaign against Sars-CoV-2 commenced in Italy at the end of December 2020. The first ones to receive the immunization against the virus were the health workers and the residents of nursing homes, following which the vaccine would be available for the entire population, beginning with the most vulnerable individuals. SARS-CoV2 vaccines have been demonstrated to be safe for the general population, although no data for patients with liver diseases or those having undergone liver transplantation are available so far. The present position statement AISF is an attempt to suggest, based on the published data on the impact of Sars-Cov-2 infection in patients with chronic liver disease, a possible priority for vaccination for this category of patients.